ANALISIS HUBUNGAN KINERJA APARATUR PEMERINTAH NAGARI TERHADAP PELAYANAN MASYARAKAT DI NAGARI LUNANG UTARA KECAMATAN LUNANG KABUPATEN PESISIR SELATAN: H. Mhd IKHSAN, S.E, M.M - Ikhsan, Mhd. (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2021)
The purpose of this study was to determine whether there is a relationship between the performance of the Nagari government officials to community services and to determine the level of the relationship between the performance of the Nagari government officials to community services in Nagari Lunang Utara, Lunang District, Pesisir Selatan Regency using a quantitative approach. The number of respondents in this study amounted to 80 people with the data collection technique is random sampling. The results in this study indicate that the product moment correlation from the calculation obtained a correlation coefficient of r = 0.65 where this correlation coefficient is in the numerical interval of 0.600 - 0799 which means that it shows the level of a strong relationship and the magnitude of the relationship between the performance of the Nagari government apparatus to community services from the test. significance obtained by the t value of 7.55 while the value of t table with an error rate of α = 0.05 db = n - 2 = 80 - 2 = 78 is 1.66 so that tcount> ttable is 7.55> 1.66 with Thus, based on the significant test criteria, Ha is accepted and Ho is rejected, meaning that there is a relationship between the performance of the Nagari government apparatus to community services in Nagari Lunang Utara, Lunang District, Pesisir Selatan Regency, West Sumatra Province.